Tutela coletiva e controle de políticas públicas: o processo coletivo estrutural como instrumento de tutela adequada de litígios complexos - Lopes Neto, João Damasceno (2024)
This study has originated from a practical observation: the traditional model of civil procedure (whether individual or collective) is not capable of providing a sufficiently effective and efficient treatment for disputes involving the judicial review of public policies. This type of dispute is classified as an irradiated collective litigation, presenting, therefore, a high degree of conflict and complexity, which are not well represented within the common paradigm of civil procedure. As a rule, the procedural system is characterized by the existence of a bilateral legal relationship, in which the parties are placed in opposite, antagonistic positions, and, as consequence, the activity of the magistrate consists of declaring the existence or not of the right claimed. This reality is not appropriate to the material needs of the judicial review of public policies. Is with this constatation that the proposal for a structural collective process arises. The structural collective process is a type of collective injunction that aims to treat complex collective disputes based on a flexible procedure, open to social participation and with a consensual approach. Thus, the central question we intended to answer in this study is: "Is the structural collective process an adequate instrument for the collective protection of the judicial control of public policies?" To answer this question, we have explored themes such as: the basis of collective protection and its challenges in the face of contemporary collective litigation; the difficulties faced by judicial control of public policies; the concept, characteristics, and applicability of the structural collective process, especially, within the Brazilian legal system. At the end, we aimed at pointing out not only the feasibility of using the structural collective process to control public policies in Brazil, but also its main advantages